Oxford German wordpack - Wilkin, Susan (Oxford University Press, 2000)
This "Wordpack" provides a thematic grouping of essential vocabulary from key language areas: people, house, city, and world. These areas are then broken down and arranged in topics, for example, parts of the body, family and friends, forming an easy-access, quick-reference vocabulary finder and builder. The book both supports the "Take Off in German" language learning pack and is a stand-alone product for users at all levels